Sacred Water or Safe Water? A Scientific Assessment of Drinking Water Quality at The Sunan Ampel Mausoleum, Surabaya - Annabelle Vania Wimala Sukma; Vita Nabiilah Faadiyah Rohmah; Rahmadani Wardafianti; Friska Nadia Andani; Aisyah Hadi Ramadani; Yuanita Rachmawati (Program Study of Biology, Science and Technology Faculty, UIN Maulana Malik Ibrahim Malang, 2026)
Water is a fundamental human necessity that must be available in a safe and potable form. In religious heritage contexts such as the Sunan Ampel Mausoleum in Surabaya, drinking water is not only consumed but also revered as spiritually significant, often perceived as sacred. This dual perception raises the question of whether such water is both spiritually and scientifically “safe.” This study evaluated the quality of drinking water stored in traditional clay jars and stainless steel tanks, assessed against the Indonesian Ministry of Health Regulation No. 492/Menkes/Per/IV/2010. Three samples were analyzed for physical (temperature, TDS, pH), chemical (nitrite), and microbiological (Coliform and Escherichia coli, MPN method) parameters. The stateresults showed that while temperature was relatively high (≥30 °C), other physicochemical values remained within permissible limits [TDS: 135–186 mg/L; pH: 7.79–8.05; nitrite: 0.1 mg/L]. In contrast, all samples were microbiologically contaminated, exceeding the permissible limit of 0/100 mL. These findings demonstrate that, although the water meets physical and chemical standards, it poses a significant microbiological health risk. The study underscores the importance of sanitation monitoring and simple water treatment at religious sites, reinforcing the Islamic principle of halalan thayyiban (lawful and wholesome) consumption and highlighting the integration of scientific evidence with religious belief in safeguarding public health.